2017
DOI: 10.1057/s41599-017-0040-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolving academic culture to meet societal needs

Abstract: Given today’s complex societal challenges, academia should work better with government, industry and others in offering innovative solutions that benefit our society, economy and environment. Researchers across disciplines must work together and with decision-makers to understand how science can have better on-the-ground impacts toward longer-term, resilient societal outcomes. This includes, for example, by working with end-users in problem formation and throughout research projects to ensure decision-making n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
0
17
0
3
Order By: Relevance
“…The goal is to find out whether leadership can be developed during distance education. Thus, hypotheses of Jacob (2015), Wowk et al (2017), and Kromydas (2017) about leadership in education have been confirmed. For this, models and characteristics associated with leadership and leaders have been identified, then they have been correlated with the distance learning environment to determine the presence or absence of contradictions.…”
Section: Methodsmentioning
confidence: 66%
“…The goal is to find out whether leadership can be developed during distance education. Thus, hypotheses of Jacob (2015), Wowk et al (2017), and Kromydas (2017) about leadership in education have been confirmed. For this, models and characteristics associated with leadership and leaders have been identified, then they have been correlated with the distance learning environment to determine the presence or absence of contradictions.…”
Section: Methodsmentioning
confidence: 66%
“…We then draw on findings from the research to underscore the potential for strengthening evidence-policy exchanges at specific junctures in national energy policymaking processes and conclude by reflecting on the implications for similarly challenging policy contexts. Our findings are an important addition to the growing literature on practical pathways to influence public policy (Witting, 2017), especially for researchers ill-prepared for the task by traditional academic training (Wowk et al, 2017).…”
Section: Introductionmentioning
confidence: 65%
“…In administering this framework, the primary role of researchers should be to broker knowledge rather than be the sole generators of it, giving due consideration to the inputs of different actors in the process (Cairney & Oliver, 2018). As Boswell and Smith (2017) and Wowk et al (2017) point out, doing so would entail a shift by individual researchers and academic institutions away from traditional understandings of what constitutes excellent research and seeing societal and policy impact as an integral component of this measure.…”
Section: Discussionmentioning
confidence: 99%